Peran Guru Agama dalam Mengatasi Kenakalan Siswa (Studi Multi Kasus di SMP Nurul Islam dan Smp Muhammadiyah 9 Ngemplak) Tahun 2013/2014 - Nugroho, Sunu Prasetyo; , Dr. H. Samino, M.M; , M. Muhtarom, S.H., M.H (2014)
Nurul Islam and Muhammadiyah 9 junior high schools are schools that have more religious content than do public schools. But there are problems related to students' behaviour. The problems are resulted from the failure of religious education in the schools. Sometimes religious education is the side where people blame to. PAI (education of Islam religion) teachers in both schools tried to solve the problems. The problems in this research are the kinds of students bad behaviour in Nurul Islam and muhamadiyah 9 junior high schools, the things caused students bad behaviour in both schools and what the teachers in both schools did to solve the problems occurred. The purposes of the research are to describe kinds of students bad behaviour in nurul islam and muhamadiyah 9 ngemplak junior high school, what caused students bad behaviour in both schools and the roles of PAI teachers in both schools to solve the problems occurred. The research is a filed study with case study approach. The research was held in Nurul Islam and Muhamadiyah 9 Ngemplak junior high school. The data collection technique was done by deep interview, observations, and documentation. Data analysis technique was done by collecting data, data reduction and display and concluding. The results of the research about kinds of students bad behaviour in Nurul Islam and Muhamadiyah 9 Ngemplak high school are: alpha, smoking, not doing homework, coming late, making noises in the middle of teaching process, fighting, not wearing standard uniform, cheating in examinations, dating, arguing with teachers, watching porn, tattooing hands, uploading inappropriate pictures and writing inappropriate status on social media, drunk, immoral, playing cards during classes without teacher. The caused of the problems are internal and external factors. PAI teachers' roles in solving the problems are divided in three stages. The first stage was preventive; it means prevent the students' bad behaviour. The second stage, repressive, it means to solve the bad behaviours and to prevent worst behaviour. The third stage is curative, the last act to handle students bad behaviour.